(untitled) (Biomedical Research and Therapy, 2019)
Objectives: Hypertensive heart remodeling requires the assumption of different factors, including an increase of left ventricular mass (LVM) and myocardial fibrosis. It was shown that aldosterone stimulates cardiac collagen synthesis and fibroblast proliferation. CYP11B2 is one of the genes responsible for the effects of aldosterone. Therefore, hypertensive remodeling could be partially related to the polymorphism of this gene. The purpose of this study was to assess the association of CYP11B2 polymorphism with structural remodeling by changes in geometry and myocardial density to define their role and interaction in hypertensive heart disease. Methods: The study recruited 150 men aged 45-60 with and without essential hypertension (EH), who possessed no irreversible target organ damages. Fifty of them had normal BP, 58 had EH without left ventricular hypertrophy (LVH) and 42 had EH and LVH. Each participant underwent office blood pressure measurement, echocardiography with echo-reflectivity analysis, and determination of the C-344T polymorphism of the aldosterone synthase gene CYP11B2. Results: Patients with EH and LVH differed not only by LV mass but also by larger body mass, relative wall thickness, and wider echo-reflectivity spectrum. The associations of larger end diastolic diameter with C allele, and the larger thickness of the posterior wall and interventricular septum with T allele, were revealed only in patients with EH and LVH. Conclusions: Hypertensive patients with LVH are likely to be a distinct cluster with their own genetic predisposition to hypertensive heart disease.